Heat-treated lanthanum magnesium hexaaluminate coatings exposed to molten calcium-magnesium-alumino-silicate. Issue 9 (15th June 2019) - Zeng, Jinyan; Sun, Junbin; Liang, Panpan; Yang, Xiong; Dong, Shujuan; Jiang, Jianing; Deng, Longhui; Zhou, Xin; Cao, Xueqiang
Abstract: LaMgAl11 O19 (LMA) coatings usually have a large amount of amorphous phase due to the rapid cooling during spraying, which will not benefit the service lifetime in aeroengine. Fortunately, the thermal cycling lifetime of LMA TBCs can be improved by heat treatment. Moreover, the hot corrosion degradation with calcium-magnesium-alumino-silicate (CMAS) attracts much attention recently. Therefore, to clarify the influence of heat treatment on CMAS corrosion behaviour, plasma-sprayed LMA coatings were isothermally heat-treated and then exposed to CMAS. Results indicate that heat treatment promoted a crystallization of LMA coatings, but the molten CMAS had completely penetrated into LMA coatings along the increased and widened vertical microcracks. It is the isotropic pores that determine the penetration kinetics of CMAS to LMA. CaAl2 Si2 O8 and MgAl2 O4 were the predominant reaction products in the superficial layer, while Ca3 La6 (SiO4 )6 interpenetrated with the residual LMA in the inner layer, forming a corroded bilayer for LMA coatings.